1H NMR-Based Metabolomics Reveals the Antitumor Mechanisms of Triptolide in BALB/c Mice Bearing CT26 Tumors - Li, Cheng; Li, Zhongfeng; Zhang, Tianjiao; Wei, Peihuang; Li, Nuo; Zhang, Wei; Ding, Xia; Li, Jian (Frontiers in Pharmacology, 2019)
Triptolide, the main active ingredient in Tripterygium wilfordii Hook. f., has shown promising effects against a variety of tumours. However, the molecular pharmacological mechanisms explaining the action of triptolide remain unknown. In this study, the CT26 colon tumour cell line was inoculated subcutaneously into BALB/c mice, and plasma samples were subjected to 1H NMR metabolomics analysis. The metabolic signature identified five metabolites whose levels were lower and 15 whose levels were higher in CT26 tumour-bearing mice than in normal control mice. Triptolide treatment significantly reversed the levels of nine of these metabolites, including isoleucine, glutamine, methionine, proline, 3-hydroxybutyric acid, 2-hydroxyisovalerate, 2-hydroxyisobutyrate, and low-density lipoprotein/very low-density lipoprotein. Based on the identities of these potential biomarkers, we conclude that the anti-tumour mechanism of triptolide might rely on correcting perturbations in branched-chain amino acid metabolism, serine/glycine/methionine biosynthesis, and ketone bodies metabolism.